Anti-microbic food packaging innovation from waste banana skin and durian seeds - Reno Susanto; W Revika; Irdoni Irdoni (Universitas Airlangga, 2021)
Edible film is a packaging that has the advantage of being easily degraded so that it does not cause environmental problems such as plastic waste which can pollute the environment. Edible film is considered to have good prospects for application in food ingredients, one of which is meat, because meat has a limited shelf life. The addition of antimicrobial ingredients to the edible film in the form of essential oil of basil leaves is useful for reducing microbial growth. The purpose of this study was to make edible films to extend the shelf life of frozen meat, utilize banana peels and durian seeds as the main ingredients for making edible films and use basil essential oil as an antimicrobial agent. The stages of activities carried out in this study included the preparation of raw materials for waste banana peels, durian seeds, and basil leaves. This stage includes the extraction process of each ingredient that produces pectin from banana peels, starch from durian seeds, and essential oil from basil leaves. Furthermore, the making of edible films from these raw materials varied the ratio between the mass of pectin and starch. The formed edible films were analyzed using FTIR, attractiveness test, and microbial growth testing by comparing meat coated with edible film and meat not coated with edible film. The characteristics of the edible film produced are 0.1 mm thick with a tensile strength value of 64.65 MPa - 75.34 MPa and a percent elongation value of 0.318% - 0.36%. The best edible film was produced at a ratio of 4: 1 (pectin: starch) with the addition of antimicrobials which had a film thickness of 0.1 mm with a tensile strength value of 75.34 MPa and 0.35% elongation percent.